DOI: 10.4995/thesis/10251/79740
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Tensile Behaviour of Uhpfrc by Means of Four-Point Bending Tests

Abstract: Combining the most recent technologies in concrete, Ultra-High-Performance Fibre-Reinforced Concrete (UHPFRC) arises as a promising material for the near future. UHPFRC have shown how flexible concrete can be to adapt to the ever-changing social and environmental demands. With its high flexibility composition and its mechanical properties, UHPFRC is full of both unexplored and unexploited possibilities. Engineers should take responsibility for this task. However, it is fair to acknowledge that this is not an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
(129 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, many researchers are engaging in developing various types of dog-bone shaped specimens to proof-test how specimen shape and gripping devices affect test results (Graybeal and Baby 2013; Reineck and Frettlor 2010; Denarié and Brühwiler 2015). It was observed that unnotched dog-bone shaped specimens with larger cross-sectional areas at the supports and a smooth geometry transition were helpful to avoid support failures and stress concentrations (Martínez 2017). Figure 2-8 depicts the dog-bone shaped specimen proposed in the Swiss standard (SIA2052 2014).…”
Section: Direct Tension Testmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many researchers are engaging in developing various types of dog-bone shaped specimens to proof-test how specimen shape and gripping devices affect test results (Graybeal and Baby 2013; Reineck and Frettlor 2010; Denarié and Brühwiler 2015). It was observed that unnotched dog-bone shaped specimens with larger cross-sectional areas at the supports and a smooth geometry transition were helpful to avoid support failures and stress concentrations (Martínez 2017). Figure 2-8 depicts the dog-bone shaped specimen proposed in the Swiss standard (SIA2052 2014).…”
Section: Direct Tension Testmentioning
confidence: 99%
“…12: Multiple micro-cracks of a UHPFRC specimen observed from a notched three-point bending test(Martínez 2017) …”
mentioning
confidence: 99%
“…In order to determinate the tensile strength of UHPFRC the stress-strain curves from the flexural tests have been taken as the starting point as seen in Figure 9. From the curve obtained, the key points [33] necessary to determine the tensile behaviour were determined, using the following points:…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Point 3 is the point of the ascending zone of the curve, with 97% of the highest stress. Based on these points, the tensile strength of the UHPFRC can be obtained by the following equations [33]:…”
Section: Tensile Strengthmentioning
confidence: 99%
“…Four-point bending tests were performed on prisms of size 100 × 100 × 500 mm 3 , with the loading points at beam length thirds, and the deflection at mid-span being measured by two displacement transducers on the front and back sides. The tensile response was obtained from the load vs deflection curves while using the simplified inverse analysis method that was proposed in [21,22]. This tensile constitutive model is defined by the parameters: elastic modulus (E), cracking strength (f t ), ultimate cracking strength (f tu ), and its associated strain (ε tu ).…”
Section: Flexural-tensile Strength Of Uhfprcsmentioning
confidence: 99%